Big Food, Big Problems: The Ethical Implications of Nestlé’s Impact on Public Health in Brazil - Whitney, Jael (Kansas State University. K-State Libraries, 2018)
As multinational food companies face stalled growth in Western countries, they are increasingly looking to developing economies to grow their sales. Unfortunately, in order to do this, these companies end up shifting large parts of traditional diets to so-called “problem foods” that are empirically connected to long-term health issues. One stark example of this is Nestlé’s impact on public health in Brazil through their women-only direct sales team. Business strategy is evaluated to consider how "Big Food"
Citation: Whitney, J. (2018) Big Food, Big Problems: The Ethical Implications of Nestlé’s Impact on Public Health in Brazil. Unpublished manuscript, Kansas State University, Manhattan, KS.
Kirmser Undergraduate Research Award - Individual Non-Freshman Category, honorable mention